Electromagnetic force distribution computations due to switching surge in disc-type winding - Nurul Farahwahida Md Yasid; Norhafiz Azis; Mohd Fairouz Mohd Yousof; Jasronita Jasni; Mohd Aizam Talib; Avinash Srikanta Murthy (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This manuscript discusses the computation of electromagnetic forces on a disc-type winding due to a standard switching impulse (SSI). First, the resistances, inductances and capacitances (RLC) of a 30 MVA, 33/11 kV disc-type distribution transformer were estimated to obtain the winding equivalent circuit. The transient voltage waveforms for each of the disc layers and corresponding resonances of the windings under the SSI were then obtained in time domains. Next, the axial and radial force distributions in the disc winding due to the SSI were computed. The forces on each disc layer and along the disc windings due to the SSI were computed based on the analytical and numerical methods via the finite element method (FEM) respectively. The non-uniform switching impulse voltage distribution results in non-uniform force distribution along the disc winding. The magnitude of the axially directed force on the disc winding is found to be higher as compared to the radially directed force.